2019
DOI: 10.1002/qua.25961
|View full text |Cite
|
Sign up to set email alerts
|

Pentapnictogen heterocyclic monoanions: Structure, stability, and aromaticity

Abstract: Inorganic planar ring‐shape molecules with 4n + 2 π electrons are always the focus of experimental synthesis and theoretical research due to their potential aromaticity and stability. In this work, the whole series of five‐membered heterocycle monoanions X nY5‐n− (X, Y = group 15 elements; n = 1‐4) were thoroughly investigated by means of density functional theory calculations. They all have large formation energies and HOMO‐LUMO gap energies, suggesting the potential thermodynamic and kinetic stability. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Recent reports have confirmed that it can give very reasonable structures, energies and aromaticities of different planar five-membered rings comparable to the expensive coupled-cluster calculations. 35–41 It also successfully provides strong theoretical evidence for the triplet-state aromaticity 42 and the presence of adaptive aromaticity 10–14,19–21,33,34 as well as the all-metal Baird aromaticity. 43 Full geometry optimizations were carried out by using the M06-2X functional 44 and the def2-TZVPPD basis set for all the elements, with the corresponding efficient core potentials for heavier Sb and Bi.…”
Section: Methodsmentioning
confidence: 87%
“…Recent reports have confirmed that it can give very reasonable structures, energies and aromaticities of different planar five-membered rings comparable to the expensive coupled-cluster calculations. 35–41 It also successfully provides strong theoretical evidence for the triplet-state aromaticity 42 and the presence of adaptive aromaticity 10–14,19–21,33,34 as well as the all-metal Baird aromaticity. 43 Full geometry optimizations were carried out by using the M06-2X functional 44 and the def2-TZVPPD basis set for all the elements, with the corresponding efficient core potentials for heavier Sb and Bi.…”
Section: Methodsmentioning
confidence: 87%
“…Recently, we predicted a series of inorganic five-membered heterocycles containing group 15 elements or group 15/16 elements to have p aromaticity and novel adaptive s + p dual aromaticity, respectively, by using the same theoretical method. 27,28 To evaluate the feasibility of forming an inverse-sandwich structure from the isolated ring and two Na atoms, its binding energy was calculated as E b = E total -E ring -2E Na , where E total , E ring and E Na are the total energies of the whole molecule, central ring and an isolated Na atom, respectively. Similarly, for the half-sandwich structures, E b = E total -E ring -E Ca was calculated, where E Ca is the energy of an isolated Ca atom.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we predicted a series of inorganic five-membered heterocycles containing group 15 elements or group 15/16 elements to have π aromaticity and novel adaptive σ + π dual aromaticity, respectively, by using the same theoretical method. 27,28…”
Section: Methodsmentioning
confidence: 99%